2021
DOI: 10.5414/als400545
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effect of herbal traditional medicine extract on molecular regulation in allergic asthma

Abstract: Asthma is an important global health problem, and the main cause of asthma is allergic reaction and immune system dysregulation. Airway inflammation causes bronchial narrowing, and goblet cell hyperplasia leads to mucus hypersecretion that leads to airflow obstruction and difficulty breathing. The Th2 cytokines can induce allergic asthma. Camellia, Adhatoda, and Glycyrrhiza are the traditional medicines that are used in some countries. In the current study, we evaluated three herbal extracts on airway inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Among root and leaves, root extract was found to be more cyto-protective by significantly inhibiting the pro-inflammatory cascade ( Marotti et al, 2021 ). In a very recent study the levels of IL-5, GTP, IL-13, GOT (on day 51), mRNA expression of eotaxin, CCL11, CCL24, COX-2, mucus secretion, eosinophil infiltration, and goblet cell hyperplasia was attenuated by the treatment of G. glabra was further support the same ( Sun et al, 2021 ). In summary, Glycyrrhetinic acid and glycyrrhizin prohibit tissue inflammation by extenuating reacting oxygen species (ROS) formation and have the potency to inhibit IL-3, IL-5, IL-6, IL-10, IL-12, IL-13, IL-1β, TNF- α expression, COX-2 and eotaxin ( Jahromi et al, 2019 ; Richard, 2021 ).…”
Section: Potential Health Benefit Of G Glabra As Anti-inflammatory Antiviral and Immunomodulatory Agentsmentioning
confidence: 63%
“…Among root and leaves, root extract was found to be more cyto-protective by significantly inhibiting the pro-inflammatory cascade ( Marotti et al, 2021 ). In a very recent study the levels of IL-5, GTP, IL-13, GOT (on day 51), mRNA expression of eotaxin, CCL11, CCL24, COX-2, mucus secretion, eosinophil infiltration, and goblet cell hyperplasia was attenuated by the treatment of G. glabra was further support the same ( Sun et al, 2021 ). In summary, Glycyrrhetinic acid and glycyrrhizin prohibit tissue inflammation by extenuating reacting oxygen species (ROS) formation and have the potency to inhibit IL-3, IL-5, IL-6, IL-10, IL-12, IL-13, IL-1β, TNF- α expression, COX-2 and eotaxin ( Jahromi et al, 2019 ; Richard, 2021 ).…”
Section: Potential Health Benefit Of G Glabra As Anti-inflammatory Antiviral and Immunomodulatory Agentsmentioning
confidence: 63%
“…3b). Th2 cytokines, such as IL-4, IL-5, and IL-13 can induce allergic asthma [40,41]. ELISA and RT-qPCR results revealed that OVA induction increased the levels of IL-4, IL-5, and IL-13 in BALF and lung tissues, while miR-181a-5p overexpression treatment showed an opposite trend (p < 0.01; Fig.…”
Section: Mir-181a-5p Overexpression Retarded the Development Of Asthm...mentioning
confidence: 86%
“…Furthermore, Thymus vulgaris showed effects in the modulation of mucus hypersecretion in vitro [ 29 ], while Hedera helix seems to play an important role in reducing cough [ 30 ] and to have a mucolytic activity similar to acetylcysteine [ 31 ] in human patients with bronchitis. Finally, Glycyrrhiza glabra represents one of the most used and effective compounds for asthma in Chinese traditional medicine, and it was effective in reducing ROS production, bronchial inflammation, and mucus production in a murine model of human asthma [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%